Retail investor information demand – speculating and investing in structured products. Issue 11 (1st September 2016) - Schroff, Sebastian; Meyer, Stephan; Burghof, Hans-Peter
Abstract : We study the impact of retail investor information demand on trading in bank-issued investment and leverage structured products, which are specifically designed for retail investors. Stock-specific information demand positively predicts speculative trading activity. Furthermore, we find a positive relationship between market-wide information demand and order aggressiveness and order uncertainty for speculating and investing activity. Whereas information supply is associated with speculative long positions, information demand does not induce investors to be predominantly long or short. Finally, we do not find retail investor information demand to contribute to an upward price pressure on security prices. In contrast, information supply exerts negative price pressure. Overall, retail investor trading in individual stocks is much more strongly influenced by market-wide information demand instead of firm-specific information demand. This implies a low informational efficiency of retail investor speculation and investing activity.